On the meaning of disjunction and conjunction in Lermontov’s The Demon - Kroó, Katalin (Slavica, 2024)
The paper analyzes Lermontov’s verse narrative (poema) The Demon by focusing on some clear-cut binaries, representing and suggesting, as their primary meaning, dichotomic pairs related to the system of literary characters (the Angel or Tamara vs. the Demon), evaluative concepts (e.g. good vs. evil), and notions comprising ideological views (the celestial, the earthly world, or the netherworld). The interpretation takes a distance from these definitions, examining the poetic modes of neutralizing and removing the dichotomies in the text by weakening the semantic motivation for setting and interpreting the binaries; the emergence of mono-dualistic antinomy, and the creation of equivalences of motifs and constructs of reverse symmetry with the transformation of their reference. Resulting from these strategies for meaning generation in Lermontov’s text, a shift from an axiological conceptualization of the world to the literary model of the human existential experience of the soul can be traced.